Averaging time, desaturation level, duration and extent. Issue 3 (8th September 2012) - Vagedes, Jan; Poets, Christian F; Dietz, Klaus
Abstract : Background: Pulse oximeter saturation values are usually obtained by averaging over preceding measurements. This study investigates the dynamics between the averaging time and desaturation level, duration and extent. Methods and results: Prospective observational study of 15 preterm infants. Oxygen saturation was recorded for 168 h using a pulse oximeter. The raw red-to-infrared data were reprocessed using seven different averaging times to determine the number of desaturations below four thresholds and for seven different minimal desaturation durations. The total number of desaturations <80% was 339 with an averaging time of 16 s and 1958 with an averaging time of 3 s (minimal event duration >0 s). There was a significantly lower pulse oximeter saturation nadir with the shorter averaging time, while the maximum duration was significantly longer when using a 16 s averaging time. Conclusions: When using pulse oximeters, more attention should be given to averaging time and duration of desaturations.